Cardiac Arrythmias in Acute and Chronic Renal Failure - Ali A. Handjani; Bijan Nazari (Acta Medica Iranica, 1966)
Cardiac arrythmias are frequent complications in acute and chronic renal failure and they may well account for sudden unexplained death in these patients. Based upon our recent study, we strongly believe that among other causative factors, focal degeneration of myocardium is the commonest and the most potentially dangerous cause of cardiac arrythmias. We suggest in emergency instances, ouabain to be used instead of digitalis which appears to be quite safe with dramatic results in cardiac arrythmias of these group.